LITERATUR REVIEW: EFEKTIVITAS MODIFIKASI DOKUMENTASI KEPERAWATAN (A Literature Review: Effectivities of Nursing documentation modification) - Astarini, Made Indra Ayu (JURNAL NERS LENTERA, 2018)
Introduction: Nursing documentation was a written and printed record that contained of patient health record development and was the duty and responsibility of the nurse. Incompleteness in nursing documentation was a frequent problem. This happened because poor of nurse knowledge about that, and the method used was still manual by writing. Computer Systems presented to help overcome this. Modifications with various model approaches were also necessary to improve the quality of nursing documentation. The purpose of this literature review was to examined modification method of nursing documentation to improve the quality of nursing documentation. Methods: This Literature review was done based on the issue, methodology, as well as the result equation obtained and the method used. A total of 6 articles used in this literature review were quantitative research, 3 of which were cross sectional studies. Results: In this literature review we found out that modification of nursing documentation with VIPS model can improve the quality of nursing documentation, as well as modification with computer system known as Electronic Health Record can improve the quality of nursing documentation. Discussion: Modification of nursing documentation is very important to make it easier for nurses to perform nursing documentation.